1991
DOI: 10.1007/bf01955934
|View full text |Cite
|
Sign up to set email alerts
|

Tuberculosis in children: a 13-year follow up of 1714 patients in a Belgian home care centre

Abstract: From May 1970 to September 1983, 1714 children with different forms of primary tuberculosis were referred to the paediatric home care centre (Enfants soignés au Foyer, E.S.F.) of the Brussels University Hospital St.-Pierre. They were subdivided in five groups: asymptomatic (33%), symptomatic (28%), dubious tuberculous infections (35%), high-risk contacts (3%) and unestablished diagnosis (1%). They were aged from 10 days to 19 years, and 82% of them were migrants of low socio-economic level. Fifty percent of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
2

Year Published

1993
1993
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(5 citation statements)
references
References 17 publications
0
3
0
2
Order By: Relevance
“…Standard multidrug TB regimens are remarkably well tolerated among pediatric patients, with adverse drug reactions necessitating modification of chemotherapy noted in only 1–3% of children [39], [41]–[43]. In a recent systematic review, Donald reported rates of elevated hepatic transaminases consistently lower in children on multidrug intensive phase therapy (8–10%) than adults (11–35%), with clinically evident drug induced hepatotoxicity in only 0.22–1.3% of children [44].…”
Section: Discussionmentioning
confidence: 99%
“…Standard multidrug TB regimens are remarkably well tolerated among pediatric patients, with adverse drug reactions necessitating modification of chemotherapy noted in only 1–3% of children [39], [41]–[43]. In a recent systematic review, Donald reported rates of elevated hepatic transaminases consistently lower in children on multidrug intensive phase therapy (8–10%) than adults (11–35%), with clinically evident drug induced hepatotoxicity in only 0.22–1.3% of children [44].…”
Section: Discussionmentioning
confidence: 99%
“…160,171,172,186–191 In two studies LFT were regularly evaluated in 1406 children; 187,189 AST and /or ALT levels were increased in 139 (9.9%). Jaundice occurred in five (0.22%).…”
Section: Hepatotoxicity Of Antituberculosis Agents In Children Treatementioning
confidence: 99%
“…Gastric lavage may also yield M . tuberculosis, but only in a small number of children: Toppet et al (20) found M. tuberculosis by this method in 15% of children with TB and in up to 41% in a subgroup of symptomatic cases.…”
Section: (I) a Routine Mantoux Test Among All Children Aged 12mentioning
confidence: 97%